Design and Construction of A 3-Phase Motor Rotation Direction Control Module Based on PLC And VSD - Toruan, Henry Hasian Lumban; Simanjuntak, Benrad Edwin; Suprianto; Peranginangin, Siwan Edi A. (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
This design consists of a practical module for controlling both forward and reverse rotational direction, utilizing a combination of a Variable Speed Drive (VSD) and a Programmable Logic Controller (PLC). The VSD regulates the frequency and voltage supplied to the motor, while the PLC serves as the logic control center, receiving input from the control buttons and sending instructions to the VSD. Testing was conducted on an unloaded motor to ensure optimal system operation. Rotational direction change testing was performed on an unloaded motor with speed variations of 10 Hz, 20 Hz, and 30 Hz and ACC/DEC values of 3.0, 5.0, and 7.0 seconds. The higher the motor speed frequency, the greater the time difference between the ACC and DEC values set on the inverter for 3, 5, and 7 seconds and the actual time for each setting. The higher the ACC value, the longer the stabilization time required for the motor to achieve stability at each frequency range.